Analysis of the implementation of Revenue management strategies to increase Revenue Per available room at Harris Hotel Sentul Bogor - Tri Djoko Sulistiyo; Rina Fitriana; Rini Angraini (Sean Institute, 2024)
The Revenue Management strategy is used to measure the achievement of Revenue Per Available Room in addition to the level of room income. To maximize revenue, not only increasing occupancy rates but also optimizing selling prices or room rates. The purpose of this study is to determine Analysis of the Implementation of Revenue Management Strategy on Increasing Revenue Per Available Room at Harris Hotel Sentul Bogor. The research method used is a quantitative descriptive research method. The study used a sample of 95 respondents with 17 statements. The implementation of the Revenue Management Strategy was declared GOOD with an average value (mean) of 3.21 which was in the interval 2.51 – 3.25. This shows that the Harris Hotel Sentul Bogor has implemented a good strategy in the field of Revenue Management. Revenue Per Available Room is HIGH with an average (mean) value of 2.97 which is in the interval 2.51 – 3.25. This shows that it is a tourist attraction. This illustrates that the achievement of Revenue Per Available Room at Harris Hotel Sentul Bogor has been carried out well. Revenue Management Strategy (X) has an effect of 61.9% on Revenue Per Available Room (Y). While the remaining 38.1% is influenced by other variables not examined.